Relevansi Pemikiran KH. Hasyim Asy’ari Tentang Pendidikan Karakter di Era Modern - Firdausy Aulia; Arbai’yah Yusuf; Wanda Nur Hanifa; Intan Cantika Arianti (Universitas Palan, 2024)
Character education has become an important conversation in the context of global education, especially in this modern era. The contribution of ideas by KH Hasyim Asy'ari, on the relevance of character education in the current context, has its own advantages. This article discusses his thoughts which emphasize universal values such as honesty, simplicity and social awareness as the main foundations of character education. This thinking is not only relevant in a traditional context, but also has strong applicability in facing the dynamics of complexity in the modern era. KH's approach. Hasyim Asy'ari in character education emphasizes the importance of forming strong morals as the main foundation in building individuals who are responsible and have integrity. Character education does not only focus on religious values, but also emphasizes the importance of developing moral and ethical aspects that are relevant in everyday life. The purpose of this research is to find out that character education from KH's perspective. Hasyim Asy'ari does not only apply to that era but can also be applied to the modern era. In the modern era full of technological changes and globalization, the values emphasized by KH. Hasyim Asy'ari such as determination, tolerance and justice have deep relevance in facing the complex challenges faced by the younger generation. Character education inspired by his thoughts is able to help the current generation to face changes and challenges that continue to develop.